Evidence for proactive interference in the focus of attention of working memory - Carroll, Lauren M.; Jalbert, Annie; Penney, Alexander; Neath, Ian; Surprenant, Aimée M.; Tehan, Gerald (My University, 2010)
Proactive interference (PI) occurs when an earlier item interferes with memory for a newer item. Whereas some researchers (e.g., Surprenant & Neath, 2009a) argue that PI can be observed in all memory systems, some multiple systems theorists (e.g., Cowan, 1999) propose that items in the focus of attention of working memory are immune to PI. Two experiments tested whether PI occurs when the to-be-remembered items are assumed, by multiple-systems theorists, to be held in the focus of attention. In each experiment, subjects saw four trials in a row with the same type of to-be-remembered items, followed by four trials in a row with a different type of material. On each trial, only 3 stimuli were shown, which is below the capacity limit of the focus of attention, and subjects were asked if a probe item was one of those 3 items seen. In both experiments, response time increased from Trial 1 to Trial 4, suggesting that items from the earlier trials interfered with memory on the later trials. In addition, release from PI was shown in that response times decreased with a change of materials. The results replicate those first reported by Hanley and Scheirer (1975), and pose a problem for theorists who argue that parts of short-term memory are immune to PI.
Keywords: focus of attention; working memory; proactive interference